2021
DOI: 10.1007/s11740-020-01009-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of degree of deformation on welding pore reduction in high-carbon steels

Abstract: Locally adapted properties within a machine component offer opportunities to increase the performance of a component by using high strenght materials where they are needed. The economic production of such hybrid components on the other hand represents a major challenge. The new tailored forming process chain, which is developed within the collaborative research center (CRC 1153) represents a possible solution to produce hybrid components. This is made possible by the use of pre-joined hybrid semi-finished prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In Ref. [38], the possibilities of porosity assessment in padding welds made using the plasma powdered arc method are presented. It was found that the use of ultrasonic waves in the range of 30-110 MHz allows the efficient detection of pores.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [38], the possibilities of porosity assessment in padding welds made using the plasma powdered arc method are presented. It was found that the use of ultrasonic waves in the range of 30-110 MHz allows the efficient detection of pores.…”
Section: Introductionmentioning
confidence: 99%